Frequency linewidth and decay length of spin waves in curved magnetic membranes - Otalora, J. A.; Kakay, Attila; Lindner, J.; Schultheiss, H.; Thomas, Andy; Fassbender, Juergen; Nielsch, Kornelius (Physical Review B, 2018)
The curvature of a magnetic membrane was presented as a means of inducing nonreciprocities in the spin-wave (SW) dispersion relation [see Otálora et al. Phys. Rev. Lett. 117, 227203 (2017)PRLTAO0031-900710.1103/PhysRevLett.117.227203 and Otálora et al. Phys. Rev. B 95, 184415 (2017)2469-995010.1103/PhysRevB.95.184415], thereby expanding the toolbox for controlling SWs. In this paper, we further complement this toolbox by analytically showing that the membrane curvature is also manifested in the absorption of SWs, leading to a difference in the frequency linewidth (or lifetime) of counterpropagating magnons. Herein, we studied the nanotubular case, predicting changes of approximately greater than 10% and up to 20% in the frequency linewidth of counterpropagating SWs for a wide range of nanotube radii ranging from 30nm to 260nm and with a thickness of 10nm. These percentages are comparable to those that can be extracted from experiments on heavy metal/magnetic metal sandwiches, wherein linewidth asymmetry results from an interfacial Dzyaloshinskii-Moriya interaction (DMI). We also show that the interplay between the frequency linewidth and group velocity leads to asymmetries in the SW decay length, presenting changes between 10% and 22% for counterpropagating SWs in the frequency range of 2-10 GHz. For the case of the SW dispersion relation, the predicted effects are identified as the classical dipole-dipole interaction, and the analytical expression of the frequency linewidth has the same mathematical form as in thin films with the DMI. Furthermore, we present limiting cases of a tubular geometry with negligible curvature such that our analytical model converges to the case of a planar thin film known from the literature. Our findings represent a step forward toward the realization of three-dimensional curvilinear magnonic devices.
CRIS-Team Scopus Importer:2022-04-14